Dielectric and electrostrictive properties of ferroelectric relaxors - SUROWIAK, Z.; FRESENKO, E. G.; SKULSKI, R. (Archives of Acoustics, 1999)
On the basis of ferroelectric relaxors electrostrictive ceramics has been obtained. Searching for electrostrictive ceramic transducers with optimal electromechanical parameters include the following: 1) investigation of different types of complex oxides with the perovskite structure (OPS): ferroelectric, antiferroelectric, non-polar; 2) investigation of OPS with different degree of the cation order; 3) measurements of the electrostrictive coefficient (Q), Curie-Weiss constant (C), coefficient of linear thermal expansion (λ), polarization (P) and permittivity (ϵ); 4) X-ray structure analysis. The following rules have been stated out during the experimental investigations: 1) values of the electrostrictive coefficients (Qijkl) depend not only on the chemical constitution of OPS but, first of all, on the degree of cation order (i.e. the coefficients increase with an increase in the degree of cation order: non-ordered state - simple state - ordered state; 2) products of the hydrostatic electrostrictive coefficient (Qh) and the Curie-Weiss (C) constant of all ferroelectric and antiferroelectric OPS are nearly equal; 3) value of the hydrostatic electrostrictive coefficient (Qh) is nearly proportional to the linear thermal expansion coefficient square (λ2). Taking into account the above mentioned rules the detailed and systematic investigations of OPS with non-ordered cations and high value of the Curie-Weiss constant (C) and permittivity (ϵ) were carried out. In such OPS high value of induced polarization leads to considerable electrostrictive deformation described by the Mijkl tensor (Mijkl ≈ Qijklϵ2r). One can mention PbNb2/3Mg1/3O3 and solid solution prepared on the basis of PbNb2/3Mg1/3O3 as an example. Devices fabricated on the basis of electrostrictive ceramics provide a relative displacement of about 10-3 what is few times more than the one provided by devices on the basis of piezoelectric ceramics.